THE REPRESENTATION OF DA‘WAH VALUES IN THE DIALOGUE AND VISUALS OF THE FILM “CINTA DALAM IKHLAS” - Afriliani; Abdur Razzaq; Anang Walian; Muhamad Afdoli Ramadoni (Indonesian Journal of Islamic Communication, 2025)
This study, entitled “The Representation of Da‘wah Values in the Dialogue and Visuals of the Film Cinta dalam Ikhlas,” aims to analyze the da‘wah values conveyed through character dialogues and their visual representations using Roland Barthes’ semiotic analysis. The research employs a qualitative descriptive method with a semiotic approach that examines signs through three levels of meaning: denotation, connotation, and myth. Primary data were collected through screenshots of selected film scenes, while secondary data were obtained from library research, including relevant books, academic journals, and scholarly articles. Data collection techniques involved repeated observation of the film and visual documentation. The findings indicate that the film Cinta dalam Ikhlas represents several core da‘wah values: (1) seeking guidance from Allah, (2) hijrah toward becoming a better individual, (3) love for the sake of Allah, (4) mutual assistance in goodness as an expression of ukhuwah islamiyah, (5) devotion to parents, (6) human effort (ikhtiar), and (7) sincere acceptance of Allah’s decree. This study contributes to the development of aesthetically grounded and meaningful visual media-based da‘wah strategies.